Pengaruh Pemberian Kromium (III) Klorida Terhadap Kadar SGPT Darah Mencit Putih - Dharma, Surya; BP, Zesfin; H, Irsan Ryanto; Zubir, Nasrul (Fakultas Farmasi Universitas Andalas, 2010)
The researh has been done on the influence of giving chromium (III) chloride on white mice blood SGPT.  The researh was divided into 5 groups, that is control,  doses ( 5,2; 6,37 and 7,8 ug/20 BW) with vitamin C and the dose of 7,8 ug/20 g BW without vitamin C. The observation was done for 42 days, that is day 7 th, 21 st and 42 nd with parameter SGPT concentration level. Results indicated that all doses showed the increase in SGPT concentration significantly (p<0,05).